Robust adaptive phase‐only beamforming algorithm for interference suppression. (24th November 2014) - Lu, Chengjun; Sheng, Weixing; Han, Yubing; Ma, Xiaofeng
Summary The adaptive phase‐only beamforming technique is very important for suppressing interferences in phased array radar. However, similar to the conventional beamforming technique, which features variable magnitudes and phases, the performance of phase‐only beamforming is severely degraded by steering direction and array geometry errors. No studies on this problem are available. In this paper, the problem of adequate robustness for adaptive phase‐only beamformers is investigated, and a robust phase‐only beamforming algorithm based on semidefinite relaxation is proposed. This algorithm can suppress interferences by minimizing the array output power and maintain the desired signal without distortion. Robust adaptive phase‐only weighting is first converted into a non‐convex quadratic optimization problem and then into a convex optimization problem by the semidefinite relaxation technique, which can be solved easily. Experimental results demonstrate that the new robust adaptive phase‐only beamforming algorithm can significantly reduce performance degradation caused by various array errors. Copyright © 2014 John Wiley & Sons, Ltd.